2017
DOI: 10.1002/ep.12592
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biochar and its effects on the water holding capacity of loamy sand soil: Comparison of hemlock biochar and switchblade grass biochar characteristics

Abstract: Two of the most important resources in agriculture are soil and water. The quality of the soil determines the health and output of crops. Biochar has been recognized as being a useful soil amendment due to its perceived benefits of increasing water and nutrient retention. However, limited research has been conducted to compare the characteristics of biochar created from different feedstocks to determine which are the most effective at raising water holding capacity. This study compared the water holding capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 7 publications
0
27
0
1
Order By: Relevance
“…Another important property is WHC since crops can uptake water and nutrients . All studied biochars present WHC higher than 300%.…”
Section: Resultsmentioning
confidence: 99%
“…Another important property is WHC since crops can uptake water and nutrients . All studied biochars present WHC higher than 300%.…”
Section: Resultsmentioning
confidence: 99%
“…It was noted that biochar could have a superior capacity to quickly adsorb Na+ on its exchange site, leading to dropping Na+ balance content in soil solution. Moreover, higher water holding capacity of biochar can trigger dilution of salt and thus decrease osmotic stress [ 41 ]. In addition, biochar can augment inorganic content in soil solution by releasing mainly K + , Ca 2+ , and Mg 2+ , resulting in declining Na + absorption in crops.…”
Section: Discussionmentioning
confidence: 99%
“…Soil amendment with biochar (product obtained from pyrolysis of agricultural materials) has found to be a sustainable organic additive to sequester carbon from environment, enhanced moisture holding capacity, and improved soil health and quality by improving cation exchange capacity organic matter status and soil fertility by nutrient retention and stimulating microbial activities in soil (Zheng et al 2010;Minhas et al 2020). The physio-chemical changes of soil due to incorporation of biochar are dependent on biochar nature, its porosity, pyrolysis conditions, application methods and applied rates (Omondi et al 2016;Yu et al 2017). Yu et al (2017) reported that plant water relations can be improved by biochar addition by lowering soil evaporation and increased tolerance against water stress condition.…”
Section: Introductionmentioning
confidence: 99%
“…The physio-chemical changes of soil due to incorporation of biochar are dependent on biochar nature, its porosity, pyrolysis conditions, application methods and applied rates (Omondi et al 2016;Yu et al 2017). Yu et al (2017) reported that plant water relations can be improved by biochar addition by lowering soil evaporation and increased tolerance against water stress condition. Minhas et al 2020 stated that biochar addition significantly enhanced the biomass and yield compared with soil without biochar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation